2011
DOI: 10.1002/14651858.cd000978.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing oral mucositis for patients with cancer receiving treatment

Abstract: Background Treatment of cancer is increasingly more effective but is associated with short and long term side effects. Oral side effects remain a major source of illness despite the use of a variety of agents to prevent them. One of these side effects is oral mucositis (mouth ulcers). Objectives To evaluate the effectiveness of prophylactic agents for oral mucositis in patients with cancer receiving treatment, compared with other potentially active interventions, placebo or no treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
115
1
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 282 publications
1
115
1
8
Order By: Relevance
“…Postoperative CT scans were done and 17 (26.2%) patients subjected to further surgery. The indications for reoperation were significant residual empyema [12], significant new collections [3], associated intraparenchymal abscess [1], and associated posterior fossa SDE evacuation [1]. All patients with CSOM/paranasal sinusitis were referred at discharge to a specialist ENT surgeon for further management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative CT scans were done and 17 (26.2%) patients subjected to further surgery. The indications for reoperation were significant residual empyema [12], significant new collections [3], associated intraparenchymal abscess [1], and associated posterior fossa SDE evacuation [1]. All patients with CSOM/paranasal sinusitis were referred at discharge to a specialist ENT surgeon for further management.…”
Section: Resultsmentioning
confidence: 99%
“…Associated supratentorial abscesses (seen in 10 cases: 15.4%) did not bear significantly on outcome unlike certain other series on SDE [12,13,14]. Early diagnosis of intracranial SDEs is pivotal to avoid significant morbidity and mortality [7, 15]; a shorter history was usually noted for patients who expired.…”
Section: Discussionmentioning
confidence: 96%
“…The adverse GI responses to chemotherapy impose an economic burden [2], delay the therapy in some cases and are the limiting factor in deciding the maximum tolerated dosage for many chemotherapeutic agents, thereby limiting the efficacy of treatment. A recent Cochrane review [3] of 131 randomized trials of agents to prevent CIM found that 10 agents provided some protection ( Aloe vera , amifostine, cryotherapy, granulocyte-colony stimulating factor, intravenous glutamine, honey, keratinocyte growth factor, laser, polymixin/tobramycin/amphotericin antibiotic pastille/paste and sucralfate), but none has achieved universal acceptance and the protective effects reported were modest, which leaves room for the development of new, more effective strategies. It may be that combinations of agents with different mechanisms of action could provide additional protection, but studies to determine this require careful preclinical and clinical trials to document their efficacy, which highlights the need for animal models that accurately reflect the human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Pentoxifylline (PTX) has been suggested for prophylaxis or treatment of oral mucositis during radiotherapy, despite lacking evidence for a beneficial effect [20,21]. PTX is a methylxanthine derivative with rheological effects, which is widely used to treat peripheral vascular diseases [22] and also has significant anti-inflammatory activity [23][24][25][26].…”
mentioning
confidence: 99%
“…PTX was also found to reduce chemotherapy-induced intestinal mucositis [34] and chemotherapy-induced oral mucositis by attenuated cytokine synthesis in a hamster model [35]. The administration of PTX has been suggested for prophylaxis or treatment of oral mucositis during radiotherapy for head-and-neck malignancies, despite lacking evidence for a clear beneficial effect [20,21]. The present study was therefore initiated to assess the effect of PTX, given over varieffect was observed for PTX application exclusively in week 2 (protocol 7/13), with an ED 50 value of 18.6 ± 2.2 Gy (p = 0.0137).…”
mentioning
confidence: 99%